Impact of interferon-free antivirus therapy on lipid profiles in patients with chronic hepatitis C genotype 1b - Endo, Daisuke (World J Gastroenterol, 2017)
AIM: To investigate the influence of interferon-free antivirus therapy on lipid profiles in chronic hepatitis C virus genotype 1b (HCV1b) infection. METHODS: Interferon-free antiviral agents were used to treat 276 patients with chronic HCV1b infection, and changes in serum lipids of those who achieved sustained virologic response (SVR) were examined. The treatment regimen included 24 wk of daclatasvir plus asunaprevir (DCV + ASV) or 12 wk of sofosbuvir plus ledipasvir (SOF + LDV). SVR was achieved in 121 (85.8%) of 141 patients treated with DCV + ASV and 132 (97.8%) of 135 patients treated with SOF + LDV. In the two patient groups (DCV + ASV-SVR and SOF + LDV-SVR), serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides were measured at baseline during treatment and at 4 and 12 wk after treatment. Then, longitudinal changes in lipid profiles were analyzed. RESULTS: Serum levels of TC, LDL-C, and HDL-C were significantly increased throughout the observation period in both the DCV + ASV-SVR and SOF + LDV-SVR groups. During antivirus treatment, the increases in TC and LDL-C were significantly greater in the SOF + LDV-SVR group than in the DCV + ASV-SVR group (P < 0.001). At 4 and 12 wk after the therapy, serum levels of TC and LDL-C were similar between the two groups and were significantly greater than those at baseline. Approximately 75%-80% of the increase in TC was derived from an increased LDL-C. In multiple regression analysis, the difference in therapy protocol (DCA + ASV or SOF + LDV) was an independent predictor that was significantly associated with the increase in TC and LDL-C at 4 wk of therapy. CONCLUSION: Serum cholesterol significantly increased during SOF + LDV treatment. After treatment, HCV elimination was associated with a similar increase in cholesterol regardless of the therapy protocol.